2017
DOI: 10.1007/978-3-319-64677-0_18
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Technology as s Support Infrastructure in e-Government

Abstract: The blockchain technology, including Bitcoin and other crypto currencies, has been adopted in many application areas during recent years. However, the main attention has been on the currency and not so much on the underlying blockchain technology, including peer-to-peer networking, security and consensus mechanisms. This paper argues that we need to look beyond the currency applications and investigate the potential use of the blockchain technology in governmental tasks such as digital ID management and secure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 19 publications
(25 reference statements)
0
39
0
1
Order By: Relevance
“…Therefore experimentation need to be guided by standardization to ensure convergence to a common standard. Ølnes and Jansen (2017) plea for a BCT-based platform for running various applications in e-Government. Such a shared infrastructure avoids the development of a new infrastructure by each project and enables the reuse of existing efforts.…”
Section: Shared Bc Infrastructure Providermentioning
confidence: 99%
“…Therefore experimentation need to be guided by standardization to ensure convergence to a common standard. Ølnes and Jansen (2017) plea for a BCT-based platform for running various applications in e-Government. Such a shared infrastructure avoids the development of a new infrastructure by each project and enables the reuse of existing efforts.…”
Section: Shared Bc Infrastructure Providermentioning
confidence: 99%
“…An ICT infrastructure is usually regarded as the collection of hardware and software components, including networks that are required to enable communication and interoperations between ICT systems. Ølnes and Jansen [20] have shown that the generic BCT (including the consensus and security mechanisms) are becoming platforms for many applications, such as securing document handling and other types of digital assets, gradually building a heterogeneous and growing user base. However, one challenge is how to maintain backward compatibility as well as horizontal equivalence across different combinations of capabilities.…”
Section: Blockchain In An Infrastructure Perspectivementioning
confidence: 99%
“…However, as we illustrate below, the blockchain technology is evolving beyond its primary application area and comprise platforms that already support a range of applications, including secure document and asset management in other areas, see [20]. The discussions are summarized in Table 1 above.…”
Section: The Installed Base and Blockchain Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…The world of financial services, already improved payment processing stands to gain from cryptocurrencies and smart devices able to execute transactions efficiently, with greater liquidity security between financial institutions (MacDonald, Allen, & Potts, 2016). Last but not least, government services will be enhanced by providing a greater level of decentralization by streamlining communication with citizens while digital voting systems will gain trust through greater layer of security and accountability while reducing the risk of fraud and tampering (Ølnes & Jansen, 2017).…”
Section: Introductionmentioning
confidence: 99%